Fungrim home page

Fungrim entry: 33aa62

G=n=0(1)n(2n+1)2G = \sum_{n=0}^{\infty} \frac{{\left(-1\right)}^{n}}{{\left(2 n + 1\right)}^{2}}
G = \sum_{n=0}^{\infty} \frac{{\left(-1\right)}^{n}}{{\left(2 n + 1\right)}^{2}}
Fungrim symbol Notation Short description
ConstCatalanGG Catalan's constant
Sumnf(n)\sum_{n} f(n) Sum
Powab{a}^{b} Power
Infinity\infty Positive infinity
Source code for this entry:
    Formula(Equal(ConstCatalan, Sum(Div(Pow(-1, n), Pow(Add(Mul(2, n), 1), 2)), For(n, 0, Infinity)))))

Topics using this entry

Copyright (C) Fredrik Johansson and contributors. Fungrim is provided under the MIT license. The source code is on GitHub.

2021-03-15 19:12:00.328586 UTC